Ethics and law for social workers - Johns, Robert (Sage, 2016)
"How do social workers in the UK legal context act ethically? What do we understand by ethics and how does social work law relate to it? Social work practice in all countries incorporates a clear, unstinting commitment to social justice, but what is social justice? Using an applied, practice-based and refreshingly 'real' approach, this text bridges the gap between law and ethics. Each chapter open with a case study which considers ethical dilemmas in real life practice. Chapters have been designed to help students strengthen their critical reflection skills, encouraging consideration of the legal and ethical dimensions of social work generally and in personal practice. Through an examination of topics such as care proceedings, adoption, community care, youth justice, mental capacity and accountability the book demonstrates how understanding both ethical theory and its application to practice are equally important"--Back cover.